Kombinasi Algoritma Vigenere dan Beaufort Cipher dalam Mengamankan Script Coding - Ilham, Ilham; Hasugian, Abdul Halim (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Cryptography has become an essential aspect in ensuring the security of information and data, especially in the context of script coding that contains secret codes that need to be kept confidential. The problem faced is securing script coding so that it cannot be accessed or modified by unauthorized parties. In this research, we propose the use of a combination of the Vigenere and Beaufort Cipher algorithms to secure script coding. The proposed method involves encrypting and decrypting script coding using both cryptographic algorithms simultaneously. The Vigenere Cipher algorithm is used to protect the integrity and confidentiality of script coding, while the Beaufort Cipher is used as an additional layer to enhance security and prevent attacks. This method is implemented and evaluated using a number of script coding samples that include sensitive secret codes. The results of the method implementation show that the combination of the Vigenere and Beaufort Cipher algorithms successfully improves the security level of script coding. Script coding encrypted using both algorithms becomes difficult to read and modify by unauthorized parties. Additionally, the encryption and decryption processes of script coding run quickly and efficiently, without impeding system performance. This research makes an important contribution to the field of information security, particularly in securing script coding. The combination of the Vigenere and Beaufort Cipher algorithms can be considered an effective solution in maintaining the confidentiality and integrity of sensitive script coding.